Effectiveness of Ultrasound Modality In Ankle Sprain - Yohan Putri, Afifah Jasmine; Kusuma, Rhona Aziza; Alpiah, Dini Nur (International Journal of Social Research, 2024)
Ligament tears often occur as a result of physical injuries, such as falling, kicking something, so they commonly occur in athletes such as football, basketball, volleyball and other sports. The aim of this research is to determine the effectiveness of ultrasound to reduce pain in Ankle Sprain sufferers. The research method used is a literature review approach, by searching for PICO method references in the Google Scholar database over a period of 10 years. There were 5 journals that met the criteria showing that ultrasound can reduce pain and increase functional ability in ankle sprains with a frequency of 0.5 to 3.5 MHz which is then converted into mechanical energy with the same intensity of up to 3.5 W /Cm2. Conclusion : the study confirms that ultrasound is an important method for assessing the fascial layers of the foot because it provides an excellent anatomical image